(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The paper, based on the approach of social determinants of health, examines the intricate relationship between migration experiences, health inequalities and safety at work. It critically reflects on the factors contributing to the higher risk of workplace injuries among migrant workers, linking these causes to the ‘context’ in which migrants find themselves living and working in the host country. The article highlights the limitations of the current Italian immigration law and also explores potential solutions within occupational health and safety legislation in order to guarantee the comprehensive ‘well-being’ to migrant workers in their workplace.